2021
DOI: 10.1111/ppc.12843
|View full text |Cite
|
Sign up to set email alerts
|

Experience and support of Chinese healthcare professionals as second victims of patient safety incidents: A cross‐sectional study

Abstract: Purpose To describe the experience and support of Chinese healthcare professionals as second victims of PSIs. Design and Methods A cross‐sectional study with anonymous online self‐report questionnaires was adopted. A total of 1357 Chinese healthcare professionals participated in this study. The Chinese version of the Second Victim Experience and Support Tool (C‐SVEST) was used to evaluate the experience of second victims and the quality of support resources. Descriptive and inferential statistics were employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
(112 reference statements)
2
9
0
Order By: Relevance
“…In our study, the prevalence of adverse events was approximately 45.26%, and previous surveys showed that the rate was 25.8%-45.3% in China (Yan et al, 2021;Zhang et al, 2019). As this study confirms, second victims who experience adverse events also encounter various degrees of negative physical, psychological and occupational impacts, which corresponds with previous studies (Busch et al, 2019;Stovall et al, 2020) 3.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the prevalence of adverse events was approximately 45.26%, and previous surveys showed that the rate was 25.8%-45.3% in China (Yan et al, 2021;Zhang et al, 2019). As this study confirms, second victims who experience adverse events also encounter various degrees of negative physical, psychological and occupational impacts, which corresponds with previous studies (Busch et al, 2019;Stovall et al, 2020) 3.…”
Section: Discussionsupporting
confidence: 90%
“…The literature on second victim syndrome has mostly emphasized/ related symptom severity among nurses working in secondary/tertiary institutions (Yan et al, 2021); conversely, we focused on nurses working in regional hospitals, analysing the degree of the second victim syndrome and their desired forms of support.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies where the results of adverse events have been addressed have traditionally been based on detecting and evaluating psychological effects (presence of anxiety, depression, stress, burnout, or especially post-traumatic stress disorder [PTSD]) 8,9,[39][40][41] . While these psychological problems are closely related to the phenomenon of second victims, they are not exclusive to it.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39] Most of the studies where the results of adverse events have been addressed have traditionally been based on detecting and evaluating psychological effects (presence of anxiety, depression, stress, burnout, or especially posttraumatic stress disorder). 8,9,[40][41][42] Although these psychological problems are closely related to the phenomenon of second victims, they are not exclusive to it. In our opinion, one of the strengths of the SVEST questionnaire is that it includes other important aspects related to the issue of second victims, such as professional self-efficacy, absenteeism, or intention to leave the profession.…”
Section: Discussionmentioning
confidence: 99%